The evolution of Leszek Kołakowski’s religious thought - Czyzewski, H (2019)
This thesis examines the entire work of the Polish philosopher Leszek Kołakowski (1927–2009), and argues that religious questions were at the heart of his thought from the very beginning of his intellectual career. Furthermore, it maintains that Kołakowski’s youthful engagement with Communism in Stalinist Poland, along with his later historical inquiries into various strands of modern philosophy were, in fact, phases in his development as a religious philosopher. The thesis, which relies on a textual analysis of Kołakowski’s published and unpublished works, argues that the investigation of consecutive texts from the late 1940s to the late 1980s shows a gradual ‘evolution’ in Kołakowski’s attitude to religion – developing from a militant Stalinist to a conservative apologist for Christianity. To this effect, the thesis is structured chronologically. The methodology employed is that of ‘qualified contextualism’, which recognises the fundamental importance of historical context in investigating philosophical questions, yet acknowledges that traditional contextualism does not suffice in explaining the ideas from the past. The entire intellectual trajectory of Kołakowski can be summarised as the quest for the most satisfactory formula for an Absolute being that not only serves as the source of ethical normativity but also endows human lives with a sense of meaningfulness. In his studies of secular philosophical systems, Kołakowski asserts that people cannot establish moral values for themselves and need a transcendent metaphysical reality. Although he was a sympathiser, Kołakowski never officially committed to any institutional form of religion. The apparent Christian synthesis between the concepts of a loving Person and an eternal Absolute seemed irreconcilable for him. It is on these grounds that this thesis concludes the mature Kołakowski can be called a religious thinker, but not a Christian thinker. ‘Kołakowski’s God’ is a being that is closer to the Neoplatonic Absolute, one that overcomes contingency of human life and makes it meaningful.